Islamic Education Curriculum Development Approach in the Digital Era: Integration of Tauhid Values and Contextual Adaptation - Sabila Qurrota A'yun; Siti Musfiroh; Romlah Romlah; Abdurrahman Abdurrahman (Andragogi: Jurnal Pendidikan dan Pembelajaran, 2025)
This study aims to deeply analyze the changes in values in the digital era by using the principle of monotheism as the philosophical, epistemological, and axiological basis in the development of Islamic Education curriculum. By applying the Systematic Literature Review (SLR) approach, this study collects, evaluates, and summarizes literature from both domestic and international sources published between 2019 and 2024, which clearly discusses the relationship between science, ethics, humanity, and digital technology. Data collection was carried out from leading databases such as Scopus, Web of Science, SpringerLink, and Garuda and DOAJ Indonesia, with strict selection based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) criteria. The analysis was carried out using thematic analysis to identify three main themes: the dimensions of scientific values, ethical principles in the digital world, and their impact on humanity and Islamic education in the digital era